MODERN TYPES OF IMMUNOENZYME ANALYSIS METHODS OLD PROBLEMS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Pyelonephritis is one of the most common inflammatory kidney diseases, frequently leading to hospitalization and chronic complications. Effective diagnostic methods are essential for the timely detection and treatment of this condition. Modern laboratory techniques, including cytokine analysis, provide valuable data for assessing the inflammatory process and predicting the disease course.